The relationship between workload, organizational support, work environment and employee performance during work from home - Nur Damayanti; Fakhri Rabialdy; Donny Abdul Latief Poespowidjojo (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This study examined the relationship between workload, organization support, work environment, and employee performance among 146 employees who work from home in Jakarta, Indonesia. The Statistical Package for Social Science (SPSS) version 24.0 was used for data analysis. Statistical results reveal a significant positive relationship between workload and work environment with employee performance. Meanwhile, organizational support is not significantly related to employee performance. For implication, management should reconsider their practice to determine the best way to support and address the needs of employees working from home as organizational support. Leaders and management must monitor and evaluate the flow of organizational support, and the results can be used as input to provide organizational support to the employee. For further researchers interested in continuing this research, it is expected to develop, namely transformational leadership and motivation